2019
DOI: 10.14814/phy2.13961
|View full text |Cite
|
Sign up to set email alerts
|

Delaying latency to hyperbaric oxygen‐inducedCNSoxygen toxicity seizures by combinations of exogenous ketone supplements

Abstract: Central nervous system oxygen toxicity (CNS‐OT) manifests as tonic‐clonic seizures and is a limitation of hyperbaric oxygen therapy (HBOT), as well as of recreational and technical diving associated with elevated partial pressure of oxygen. A previous study showed that ketone ester (1,3‐butanediol acetoacetate diester, KE) administration delayed latency to seizures (LS) in 3‐month‐old Sprague‐Dawley (SD) rats. This study explores the effect of exogenous ketone supplements in additional dosages and formulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…Several discussions on how to evaluate oxygen toxicity in humans are ongoing, and a matter of debate; newly developed approaches have been very recently analyzed, implying new calculations, markers, and also dietetic approaches [54][55][56][57]. In our setting, it is very complicated to set direct links between pulmonary and neurological oxygen toxicity from a clinical point-of-view.…”
Section: Oxygen Toxicitymentioning
confidence: 99%
“…Several discussions on how to evaluate oxygen toxicity in humans are ongoing, and a matter of debate; newly developed approaches have been very recently analyzed, implying new calculations, markers, and also dietetic approaches [54][55][56][57]. In our setting, it is very complicated to set direct links between pulmonary and neurological oxygen toxicity from a clinical point-of-view.…”
Section: Oxygen Toxicitymentioning
confidence: 99%
“…Subjects report difficulty maintaining ketosis as excess consumption of carbohydrates or protein can rapidly shift the body back towards glycolysis and inhibit ketogenesis [ 13 ]. Alternative solutions to achieving nutritional ketosis are needed, and exogenous ketone supplementation has been reported to be an effective alternative to KD in the context of various disease states [ 11 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ketone supplementation that contains either KE, ketone salt (KS), medium chain triglycerides (MCTs), or their combinations (e.g., KEKS, KEMCT, and KSMCT) has been studied in both animal models and humans. It has been demonstrated that exogenous ketone supplementation is a safe and effective option to induce nutritional ketosis [ 16 , 29 , 30 , 31 , 32 ], and, consequently, evoke alleviating effects of ketosis on motor performance similar to KD [ 2 , 4 , 6 , 33 ]. Indeed, it was suggested that administration of KE and MCTs may evoke beneficial effects on motor dysfunction [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of MCTs to ketone esters or ketone salts may offer a novel way to improve or further augment their anti-seizure/neuroprotective potential (Ari et al, 2018). A combination of BHB salts and MCT oil has been administered in ratios of 1:1 to 1:2 mixtures.…”
Section: Medium Chain Triglyceridesmentioning
confidence: 99%
“…Exogenous ketone supplements have typically been studied as a single stand-alone supplement, but the unique combination MCT added to ketone salts or ketone esters appears to have pharmacokinetic advantages and favorable behavior effects (Ari et al, 2016; Kesl et al, 2016). Formulating specific supplements will likely enhance the tolerability, absorption, peak and sustained levels of ketones in the blood, which may also translate to greater therapeutic potency and anti-seizure efficacy (Kovacs et al, 2017; Ari et al, 2018).…”
Section: Medium Chain Triglyceridesmentioning
confidence: 99%